The efficiency of ultrasound-guided erector spinae plane block in early cervical cancer patients undergoing laparotomic radical hysterectomy: A double-blind randomized controlled trial - Zhou, Ling; Wang, Shan; Liu, Chunmei; Yan, Tingting; Song, Youping; Shu, Shuhua; Wang, Sheng; Wei, Xin (Frontiers in Surgery, 2023)
Aims: We aim to compare the efficiency of erector spinae plane block (ESPB) with transversus abdominis plane block (TAPB) in patients undergoing laparotomic radical hysterectomy due to little studies are reported. Methods: In this randomized controlled trail (RCT), 154 eligible patients were randomly allocated into ESPB group [ESPB + patient-controlled intravenous analgesia (PCIA)] and TAPB group (TAPB + PCIA) at 1:1 ratio. The primary outcome was visual analog scale (VAS) score at rest state at 12 h. Results: We found that ESPB group was associated with the lower VAS scores at rest and cough state than TAPB group at 2 h, 4 h, 6 h, 12 h, and 24 h postoperatively (P < 0.05). Less analgesic consumption and sufentanil consumption in PCIA pump were found in the ESPB group (P < 0.05). Moreover, ESPB group was followed by fewer rescue analgesia requirements, less rescue analgesic consumption, less adverse reactions, and higher analgesia satisfaction (P < 0.05). Conclusions: Our study found that ESPB had advantages on analgesic effect and opioids consumption. In the future, more studies were needed to confirm our findings.